A normative approach to contemporary Turkish foreign policy: The cosmopolitanism-communitarianism divide - PARLAR DAL, EMEL (SAGE PUBLICATIONS LTD, 2015)
This study explores the cosmopolitanism-communitarianism divide in normative international relations (IR) theory with a special focus on the apparent increasing weight of ethics and morality in Turkish foreign policy. First, it outlines the current debates in normative IR theory with a special focus on the divide between cosmopolitanism and communitarianism. Second, it asks whether Turkey's foreign policy tradition, both in its discourse and its ethics, leans more toward cosmopolitanism or communitarianism. Then, it examines the slow rise of cosmopolitanism in Turkish foreign policy in the 2000s, with particular reference to the ruling political party in Turkey, the AKP (the Justice and Development Party). Finally, it examines the cosmopolitan/communitarian dilemma that the AKP government faces in the context of the Arab Spring, and specifically the Syrian civil war.
Keywords: Turkish foreign policy; normative international relations (IR) theory; cosmopolitanism-communitarianism divide; global ethics; international justice; global; citizenship; global governance; Syrian crisis